PENGARUH SISTEM AKUNTANSI MANAJEMEN DAN GAYA KEPEMIMPINAN TERHADAP HUBUNGAN ANTARA TOTAL QUALITY MANAGEMENT DENGAN KEPUASAN KERJA PADA PERUSAHAAN GO PUBLIK DI BURSA EFEK JAKARTA - Sri Suranta (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
The purpose of this research is to examine empirically the effect of management accounting systems and leadership style to the relationship between Total Quality Management (TQM) with job satisfaction. The hypothesis is that there are significant influence of management accounting systems and leadership style to relationship between Total Quality Management (TQM) with job satisfaction. Taken population in this research consists of companies in Indonesian Capital Market Directory (ICMD) year 2004. The samples are middle managers of manufacturing business in ICMD. The hypotheses are examined by moderated regression analysis. Therefore, data must be analyzed by classical assumption, i.e. normality, autocorrelation, and heteroscedasticity. The examination indicated that all variable are valid and reliable. The classical assumption test fulfilled the classical assumption. Results of hypothesis examination indicate that leadership style has effect to the relationship between Total Quality Management (TQM) with job satisfaction. Nevertheless, the effect of management accounting systems to relationship between Total Quality Management (TQM) with job satisfaction is not supported by the research. Keyword: Total Quality Management (TQM), Management Accounting Systems, Leadership Style, Job Satisfaction.